The role of affixal means of the Russian language in the development of the category of aspect - Kryuchkova, Olga Yuryevna (Известия Саратовского университета. Новая серия. Серия Филология: Журналистика)
By the beginning of the written period of the Russian language, the formation of new aspectual meanings in verbs is already noticeable. The means of forming the category of aspect in the history of the Russian language are affixes: prefixes formalize the meaning of finiteness; suffixes participate in expressing the meaning of non-finiteness. The initial stage of the formation of the category of aspect is semantic transformations of prefixes. The processes of delocalization – neutralization of their initial spatial meanings – are developing in prefixes, and the semantic function of expressing the meaning of general result is being formed. This process is accompanied by the development of prefixal synonymy, semantically duplicating secondary prefi xation in verbs with a general resultative meaning. The aspectual function of the prefixes, which originally had a vaguely expressed perfective meaning, was strengthened by the development of special means of imperfectivation, such as a variety of suffixes (with the suffix -iva/-yva prevailing). The competition of suffixal means of imperfectivation is expressed in the development of variation, secondary duplicate suffixation in the circle of imperfective verbs, and changes in the aspectual function of suffixal verbs. Along with the stabilization of the means of expressing the imperfective meaning, the aspectual (perfective) meaning of prefixes is strengthened. A notable role in this process belongs to secondary prefixation as a means of removing the bi-aspectual meanings of prefixal verbs. Suffixes and prefixes play a crucial role in the formation of the aspectual system of the Russian language. However, the nature of their participation in the formation of the category of aspect in Russian is different. In the history of the Russian language special suffixes of imperfectivation appear, there are no special aspect forming prefixes, prefixes undergo a change in terms of content, they acquire the ability to act not only in the function of a word-forming, but also an aspect-forming means. The history of the formation of the category of aspect in Russian indicates its morphological-derivational character.